Drift Characteristics of DONET Pressure Sensors Determined From In-Situ and Experimental Measurements - Matsumoto, Hiroyuki; Araki, Eiichiro (Frontiers in Earth Science, 2021)
DONET, the dense ocean-floor network system for earthquakes and tsunamis began operations in the Nankai Trough, SW Japan in 2010. The present study focuses on the pressure sensors that are being used as tsunami meters to measure changes in hydraulic pressure. It is known that pressure sensors typically show a drift in their readings over their operational lifespan. The DONET pressure sensors can act as geodetic sensors measuring vertical crustal deformation change over time, if the sensor drift can be corrected accurately. This achievement to monitor crustal deformation before the occurrence of mega-thrust earthquakes is performed by discrimination between the vertical crustal deformation and the sensor drift of the pressure sensors. Therefore, here, we evaluate the sensor drift shown by the DONET pressure sensors since their deployment into the deep sea, by removing the tidal component and confirming that sensor drift has in fact taken place since deployment. We evaluated the initial behavior of pressure sensors before deployment into the deep sea, using our own high-accuracy pressure standard. Our experiment involved the pressurization of 20 MPa to the pressure sensors under an ambient temperature of 2°C, for a duration of one month. Some sensor drifts in our experiment correspond in rate and direction to those from the in-situ measurements determined to be in the initial stage. Our experiment suggests that the pre-deployment pressurization of pressure sensors can be an effective procedure to clarify the sensor drift after their deployment into the deep sea.